2017
DOI: 10.1111/1745-5871.12251
|View full text |Cite
|
Sign up to set email alerts
|

Keeping cool: practicing domestic refrigeration and environmental responsibility

Abstract: Domestic refrigerators have become symbols of climate change in energy efficiency campaigns; they are equipment that both permits and prohibits the performance of environmental citizenship. However, little is known about how subjectivities and practices interact, particularly with regard to questions about refrigeration and domestic energy. What might those of us interested in household sustainability learn from the relationships among refrigerators, energy, subjectivities, and practices, and from what these m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…We argue that the toolbox offers something different than interviews or participant observations. While interviews target sensemaking about the studied practice, and participant observation targets the practice itself, our (combination of) methods is specifically designed to make the studied practice more present in the interview and bring the elements of the interview and participant observation usefully together (see also Phillips and Waitt 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We argue that the toolbox offers something different than interviews or participant observations. While interviews target sensemaking about the studied practice, and participant observation targets the practice itself, our (combination of) methods is specifically designed to make the studied practice more present in the interview and bring the elements of the interview and participant observation usefully together (see also Phillips and Waitt 2018).…”
Section: Discussionmentioning
confidence: 99%
“…With an international growing trend of bigger and multiple appliances (Sahakian 2022), refrigerated food storage has implications for environmental sustainability, not least due to rising energy demand (Rinkinen, Shove & Smits 2017). Geographers have suggested that encouraging collective cooling practices, rather than individual, may reduce the use of refrigeration for food and air-conditioning while also making it accessible to more people (Farbotko & Waitt 2011;Phillips & Waitt 2018). Others have proposed the potential of resurrecting past practices for intervening in contemporary life and encouraging more sustainable ways of living (Maller & Strengers 2015).…”
Section: W Ould You Share Your Refrigerator or Freezer With Your Neig...mentioning
confidence: 99%
“…Fridges and freezers are involved in daily ways of living and consumption conventions that have considerable impact on the climate and 1 Creative common license CC BY-NC allows sharing and adapting the image for non-commercial purposes as long as the creator is accredited. environment; for example, through increased food waste, preferences for fresh foods, multiple appliances, and energy demand (e.g., Waitt & Phillips 2016;Phillips & Waitt 2018;Rinkinen, Shove & Smits 2019;Evans & Mylan 2019;Sahakian 2022). Collective cooling practices have been suggested in this context as a way to make refrigeration available to more people while reducing energy consumption (Farbotko & Waitt 2011;Phillips & Waitt 2018).…”
Section: Framing Collective Coldmentioning
confidence: 99%
See 1 more Smart Citation
“…Social practice theory has been applied in various studies to understand residential energy use, e.g., [21][22][23]. It has also been used for understanding everyday kitchen life [24], kitchen transformation and renewal [25], and to study the use of specific appliances within the kitchen [26,27].…”
Section: Social Practice Theorymentioning
confidence: 99%